Yin-Yang 1 transcription factor modulates ST2 expression during adverse cardiac remodeling post-myocardial infarction. (May 2019) - Asensio-Lopez, M.C.; Lax, A.; Fernandez del Palacio, M.J.; Sassi, Y.; Hajjar, R.J.; Januzzi, J.L.; Bayes-Genis, A.; Pascual-Figal, D.A.
Abstract: Background: The cardioprotective effects of metformin remain poorly defined. Interleukin (IL)-33/ST2L signaling is a novel cardioprotective pathway, which is antagonized by the soluble isoform sST2. No data exist about the regulation of ST2 expression. This study aimed to evaluate the pathophysiological implication of Yin-Yang 1 (Yy1) transcription factor in cardiac remodeling and the expression of the soluble ST2 isoform. Methods and results: Myocardial infarction (MI) was induced in Wistar rats randomly receiving metformin or saline solution by permanent ligation of the left anterior coronary artery. In addition, a model of cardiomyocyte "biochemical strain" was used. Metformin administration improved post-MI cardiac remodeling, an effect that was associated with increased IL-33 and reduced sST2 levels in the myocardium. The anti-remodeling effects of metformin were also associated with a decrease in the transcription factor Yy1 intranuclear level and lower levels of phosphorylated HDAC4 within the cytoplasmic space. These effects were also observed in a cardiomyocyte biochemical strain model, where Yy1 silencing or HDAC4 inhibition blocked sST2 production in cardiomyocytes. Metformin blocked the HDAC4 phosphorylation induced by MI, preventing its export from the nucleus to the cytosol. The presence of dephosphorylated HDAC4 in the nucleus acted as a co-repressor of Yy1, repressing sST2 expression. Conclusion: The transcription factor Yy1 regulates sST2 expression, and repression of Yy1 by metformin results in lower levels of sST2 that are associated with favorable myocardial remodeling. The manipulation of YY1 or its co-repressor HDAC4 emerge as new targets to modulate ST2/IL33 signaling and prevent adverse cardiac remodeling. Graphical abstract: Unlabelled Image Highlights: No data exist about the regulation of ST2 expression. The Yin-Yang 1 (Yy1) transcription factor modulates sST2 gene expression. HDAC4 acts as co-repressor of Yy1 and work together to modulate sST2 mRNA expression. The down-regulation of sST2 lead to a cardioprotective response.